Reprezentatywność cech gatunkowych trawelogu w porównaniu z innymi gatunkami literackimi - Rozinkewycz, Natalia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The purpose of the article is to systematize the experience of modern scholars who study the genres of travel literature. The focus is on determining the basic characteristics of travelogues in comparison to the genre features of other genres containing travel (essay, feature, guidebook, etc.). The difference between travel and geographical literature has been clarified. To distinguish between similar genres and understand the differences between them, it is necessary to identify the common and peculiar features of different genres of travel literature.
The Representativeness of the Features of Travelogue as a Genre in Comparison to Other Related Genres
Keywords: travel literature; geographical literature; semantic field of travelogue; essay; travel novel; travel essay; literatura wędrowna; literatura geograficzna; pole semantyczne trawelogu; esej; powieść podróżnicza; szkic wędrowny